2023
DOI: 10.1126/sciadv.adi5990
|View full text |Cite
|
Sign up to set email alerts
|

Viscous-capillary entrainment on bioinspired millimetric structure for sustained liquid transfer

Ziyang Cheng,
Chuxin Li,
Can Gao
et al.

Abstract: Liquid entrainment with a solid architecture passing through the fluid-fluid interface is ubiquitous and widely used in industrial processes as a liquid transfer method. Besides liquid properties, solid structures play a core role in entrainment. Although the influence of its macroscopic curvatures and microscale roughness has attracted years of research, the effect and potential of the commonly seen millimetric structures have not been sufficiently explored and exploited. Here, we demonstrate enhanced liquid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 62 publications
(67 reference statements)
0
6
0
Order By: Relevance
“…1(a)). 12,15,22,[42][43][44] Considering the tongue's enhancement effect on the air-liquid entrainment, we abstracted it as a typical model to investigate its behavior in the liquid-liquid entraining process. The experimental setup includes a 3D-printed rod as the solid object, a liquid tank containing two liquids, and a high-speed camera to record the entrainment (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1(a)). 12,15,22,[42][43][44] Considering the tongue's enhancement effect on the air-liquid entrainment, we abstracted it as a typical model to investigate its behavior in the liquid-liquid entraining process. The experimental setup includes a 3D-printed rod as the solid object, a liquid tank containing two liquids, and a high-speed camera to record the entrainment (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In summary, our study identified two primary mechanisms to hinder the upward drainage of entrained oil in our experimental setup: (1) use of spiky plates: by employing spiky plates with a high number density, we were able to pin the liquid–liquid interface effectively. This action formed periodic menisci with negative Laplace pressure, 22 thereby supporting and stabilizing the oil film above it; (2) oil film ‘necking’: another observed phenomenon was the ‘necking’ of the oil film, which constricted the passage of oil, retaining it below the necking point, as depicted in Fig. 2(d).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Next, we utilized x-ray imaging coupled with a drop-impact set-up to visualize the water film rupture and drainage on the pitcher's mouth (figure 1(d)). The real-time observations and an in-depth understanding of the mechanism can be achieved by in situ x-ray computer microtomography [46][47][48]. Our experiments involve releasing a water drop (radius R = 2.5 mm, velocity U = 1.0 m•s −1 ) onto a pitcher's mouth and filming the film rupture and drainage dynamics inside the sample chamber of Micro-CT under 25 kV x-ray tube voltage (figure 1(d)).…”
Section: X-ray Imaging For Fast Drainage Prototypementioning
confidence: 99%